30: STRONG IMPACT OF SARCOPENIA AS A RISK FACTOR OF SURVIVAL IN RESECTED GASTRIC CANCER PATIENTS: FIRST REPORT FROM AN ITALIAN CANCER CENTER. (23rd April 2022) - Ricciardolo, A A; De Ruvo, N; Prampolini, F; Pecchi, A; Missori, G; Sorrentino, L; Rossi, E G; Fenocchi, S; Salati, M; Spallanzani, A; Cautero, N; Serra, F; et al.
Abstract: Background and aim: Gastric cancer (GC) accounts for 4% of all cancers in Europe. Sarcopenia is a complex syndrome characterized by a loss of muscle mass and function associated with age, often present in neoplastic diseases. Recently several studies have shown a significant association between sarcopenia and poor prognosis in various pathological conditions. Methods: This observational retrospective study investigates the association between sarcopenia and outcome, both as RFS and OS, in patients with GC undergoing surgery with curative intent. For 50 patients, 25 male and 25 female, the preoperative CT calculation of the skeletal muscle index (SMI) at L3-level allowed us to identify 34 patients with and 16 without sarcopenia. Kaplan-Meyer and univariable and multivariable Cox regression analysis were performed to determine difference in survival and presence of independent prognostic factors. Results: A statistically significant difference between the sarcopenic and non-sarcopenic groups was observed in both overall survival (OS) and recurrence-free survival (RFS) ( P  < 0.023; P  < 0.006). Moreover, sarcopenia was strongly correlated to a higher risk of recurrence in univariate and multivariate analysis ( P  < 0.02). Conclusion: Sarcopenia can be considered a critical risk factor for survival in patients with resectable GC.